Photoisomerization of a Chiral Imine Molecular Switch Followed by Matrix‐Isolation VCD Spectroscopy. Issue 7 (12th January 2017) - Pollok, Corina H.; Riesebeck, Tim; Merten, Christian
Abstract: Characterizing the stereochemistry of transient photoisomerization products remains a big challenge for the design of molecular machines, such as unidirectional molecular motors. Often these states are not stable long enough to be characterized in detail using conventional spectroscopic tools. The structurally simple camphorquinone imine1 serves to illustrate the advantage of combining the matrix‐isolation technique with vibrational circular dichroism (VCD) spectroscopy for the investigation of photoisomerizations of chiral molecules. In particular, it is shown that both ( E )‐ and ( Z )‐1 can be generated photochemically at cryogenic temperatures in an argon matrix, and more importantly, that the stereochemistry of both switching states can be characterized reliably. Abstract : Flip the switch ! The chiroptical properties of the E ‐ and Z ‐isomers of a camphorquinone imine derivative were studied by means of matrix‐isolation vibrational circular dichroism spectroscopy. This technique can be used to characterize the switching states of chiral molecular motors.